Catostomus murivallis, a new species of sucker (Cypriniformes: Catostomidae) from Wall Canyon Creek, Surprise Valley, in Northwestern Nevada, U.S.A. - Harris, Phillip M.; Markle, Douglas F.; Campbell, Matthew A. (Zootaxa, 2025)
Since 1934 when it was originally collected by C. L. Hubbs and R. R. Miller, a Catostomus from Wall Canyon Creek has been considered a putative species. Occurring in a limited range in Surprise Valley, Washoe Co., Nevada, USA, this undescribed Wall Canyon Sucker exhibits an overall similarity to other Catostomus species that are naturally distributed in close geographic proximity. Molecular phylogenetic and population genetic studies have included the Wall Canyon Sucker and refined its relationships such that it is the sister taxon of the Warner Sucker Ca. warnerensis endemic to the Warner Basin of Oregon and closely related to the Owens Sucker Ca. fumeiventris of the Owens Valley in California. All three lineages occupy drainages just east of the Cascade Range and the Sierra Nevada mountains in western North America. Multiple genetic data sources support the separation of the Wall Canyon Sucker from Ca. murivallis and Ca. warnerensis with at least a Pleistocene division without recent gene flow. Here, we formally describe Catostomus murivallis sp. nov. from Wall Canyon Creek in Surprise Valley. Catostomus murivallis is statistically significantly different from Ca. fumeiventris and Ca. warnerensis at 16 of 34 and 17 of 34 morphometric characters investigated. Three of four and two of four meristic characters respectively were found to be significant different as well between Ca. murivallis and the two valid and closely related Catostomus species.